PENGARUH PENERAPAN MODEL DEEP LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMA KOTA BENGKULU - Syaipul Amri; Poni Saltifa; Resti Komalasari (Universitas PGRI Silampari, 2025)
This article investigates the influence of deep learning models on mathematical problem-solving abilities among high school students in Bengkulu City. The study employs a quantitative research approach with experimental design to analyze the effectiveness of implementing deep learning technology in mathematics education. The research involves 120 students from three different high schools in Bengkulu City, divided into experimental and control groups. Results indicate that students who utilized deep learning-based learning models showed significant improvement in mathematical problem-solving capabilities compared to traditional learning methods. The findings suggest that integration of technology, particularly deep learning models, can enhance students' analytical thinking and mathematical reasoning skills.